Micro-transitions et écoquartiers : la recomposition des pratiques énergétiques face aux déterminismes matériels et socio-économiques - Taoufik Souami; Ida Kasdi (VertigO)
In this article, we discuss the energy transition at the level of local social groups (individuals, households). Our hypothesis is that behavior change also operates by a set of micro-transitions that are played in individuals both consumers, residents, local users, members of defined social groups. The research was conducted in two eco-neighborhoods in France in which we analyze consumption and energy practices a few years before and after people installation. Two observations arising from the analysis of the sample. The materials expected to automatically reduce energy footprints by limiting the margins of flexibility of the inhabitants fail to meet identified targets. Population socio-economic conditions proposed to explain behavior are not operative. Three practical change strategies are indeed identified: resistance produced an increase in consumption, acceptance that stabilizes and optimization tends to reduce it. These three strategies and their results do not match any occupational group in particular. Young workers, retirees, high income, more modest, singles and families with 2 or 3 children adopt one or other of the strategies and obtain different results. These analyzes therefore invite to expand the scope of factors to be taken into account to take into account the energy transition at local social groups level. Indeed, patterns of explanation generally considered and categories used to direct reflection on the global transition seem not really operative.